Dental Treatment Data in Children Living in Areas with Elevated Fluoride Content in Water - Kamchybekova, Akmaanai; Tynalieva, Rahimat; Abykeeva, Ryskul; Erkebaeva, Akdana; Cholokova, Gulnar (International Journal of Child Health and Nutrition, 2026)
Objectives: This study aimed to comprehensively assess the dental status of children aged 5-11 years residing in areas with naturally fluoridated water. The study included 486 children, selected by age and permanent residence using randomisation in Kyzyl-Suu and a continuous survey in Orgochor. Dental status was assessed according to World Health Organization recommendations using the KPUp+kpp and KPUz+kpz indices, while oral hygiene was evaluated using the Fedorov-Volodkina index. Methods: The concentration of fluorides in drinking water was determined by the potentiometric method, with multiple samples collected at different times of day. Statistical processing of the data involved the use of the standard error of the mean (m), Student’s t-test, and quantile-quantile plots to assess distribution normality. The results showed that the prevalence of caries among children aged 5-11 years ranged from 93.1% to 100%, depending on age group and place of residence: in Kyzyl-Suu it reached 100% in all groups except 10-11 years (96.0%), while in Orgochor it varied from 93.1% (7 years) to 98.5% (10-11 years), with a clear age-related trend towards a decline in the incidence of deciduous teeth caries and a simultaneous increase in the intensity of damage to permanent teeth. Findings: In Orgochor, where the fluoride concentration was 1.44 mg/l, a moderate decrease in caries activity was observed; however, the incidence of fluorosis reached 27.3%. More than 60% of children had unsatisfactory or poor oral hygiene, which further aggravated the risk of dental diseases. The relationships identified between fluoride levels, hygiene conditions, and the prevalence of pathology indicate a complex interdependence of risk factors in the study population. Conclusions: The findings underscore the need for comprehensive sanitary control, educational programmes, and regular monitoring of drinking water quality to prevent dental diseases in paediatric populations.